Policing the Void: Recreation, Social Inclusion and the Baltimore Police Athletic League - Bustad, Jacob J. (Social Inclusion, 2017)
In this article, we explore the relationship between public recreation policy and planning and the transformation of urban governance in the context of the Police Athletic League centers in Baltimore, Maryland. In light of contemporary discussions of the role of youth programs for sport and physical activity within post-industrial cities, the origination, development, and eventual demise of Baltimore’s network of Police Activity League centers is an instructive, if disheartening, saga. It illustrates the social and political rationales mobilized in justifying recreation policy and programming, the framing of sport and physical activity as preventative measures towards crime and juvenile delinquency, and the precarity of such initiatives given the efficiency-driven orthodoxies of neoliberal urban entrepreneurialism (Harvey, 1989). This analysis emphasizes how the PAL centers were designed to ‘fill the void’ left by a declining system of public recreation, thereby providing an example of a recreation program as part of the "social problems industry" (Pitter & Andrews 1997).